Атрибутивные коллокации, как источник языковой экспликации концепта „любовь” в русском лингвокультурологическом пространстве - Sitarski, Andrzej (Acta Polono-Ruthenica, 2018)
The aim of the study is to present attributive adjectival collocations, categorizing the concept ”love” in contemporary Russian linguistic and cultural space. On the basis of semantic analysis of 130 excerpted exemplary collocations it must be stated that the realization of the concept under discussion within the analyzed language units is the result of crossing of the concept „love” with the concepts „space”, „time” and „values”, which have their semantic realization in the collocations under study. It should be emphasized that the analysis of semantics of specified collocations would not be possible without paying attention to a human being - his emotional and spiritual world, system of standards and values, as well as the feeling of love. That is why an anthropocentric paradigm has been taken into consideration in the description of the excerpted linguistic material.